Power quality monitoring and analysis / Ismail Bakar - Bakar, Ismail (1997)
Power quality exist today because of the incompatibility of the sensitive equipment to the typical power quality supplied by utility systems. Some of the sensitive loads are particularly vulnerable to short term or momentary interruptions. The increasing use of computers and other sensitive equipment, such problems will continue to grow unless correction measures are taken. This project nas been tailored to monitor and analyse all type of disturbances which might be available in the selected location in Institut Teknologi MARA and TNB Port Klang substation feeder to Jabatan Laut Selangor. This data is hopefully will indicate the source of disturbance and help in finding an improved plan for the system. It is hope that with all the records and compiled data bases, utility engineer and maintenance department can now be abte to control the quality of power system effectively.